2017
DOI: 10.3390/ijerph14060581
|View full text |Cite
|
Sign up to set email alerts
|

Transtheoretical Model of Change during Travel Behavior Interventions: An Integrative Review

Abstract: This study aims to identify the relevant empirical work, to synthesize its findings, and to thus attain a general understanding of the application of the Transtheoretical Model (TTM) in transport behavior research. An integrative literature review was used to determine whether or not the implemented interventions impact the stages and processes of travel behavior change. Data was collected from different databases. English language articles published between 2002 and 2017 were included. After sequentially narr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 41 publications
(92 reference statements)
1
30
0
Order By: Relevance
“…In addition to judgmental factors, there may very well be other psychological factors of importance for carpooling. The concept of stage of motivation or degree of intention for potential behavioral change could, for instance, be applied to determine how willing people are to use different types of carpool offerings (e.g., References [54,55]). It may then be possible to design and match interventions that attract different segments of people based on their stage of motivation to change.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to judgmental factors, there may very well be other psychological factors of importance for carpooling. The concept of stage of motivation or degree of intention for potential behavioral change could, for instance, be applied to determine how willing people are to use different types of carpool offerings (e.g., References [54,55]). It may then be possible to design and match interventions that attract different segments of people based on their stage of motivation to change.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that health behavior training can effectively reduce the occurrence of WRMDs among nurses [48,49]. In the current study, we adopted ergonomics as the theoretical guide, combined with the work characteristics of ICU nurses, and guided nurses to take a scienti c posture to engage in clinical nursing work.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results, future research should focus on designing interventions tailored to stages of change by using processes stressing the psychological mechanisms identified to be important, such as affective and instrumental attitudes, perceived behavior control, personal norm, and social norms. Distinguishing between stages and processes is essential when it comes to generating reliable results, especially since previous intervention studies often lack this kind of separation [ 4 ]. The processes under discussion originate from studies made in various contexts, e.g., health, physical activity, the environment, and energy conservation (e.g., [ 48 , 49 , 54 , 55 , 56 ]).…”
Section: Discussionmentioning
confidence: 99%
“…The documented negative impacts of car use, such as noise, congestion, pollution, and a sedentary lifestyle, provide compelling reasons to adopt and maintain sustainable travel behavior [ 3 ]. However, more knowledge is required regarding the mechanisms underlying the intention to change from a car commute to a sustainable work commute (e.g., walking, cycling, using public transport or carpooling) [ 4 ]. A better understanding of the process of change would help to clarify the posited theoretical relations and, more importantly, facilitate the development of interventions aimed at addressing and potentially reducing the car commute.…”
Section: Introductionmentioning
confidence: 99%